Original creations with papier mcachbe. - Anderson, Mildred (New York Sterling Pub. Co., 1968)
Briefly explains the technique of using papier mcachbe and gives directions for making many useful and decorative objects, such as a bead curtain, lamp shades, dishes, and a puppet theater.
Keywords: Papier-mcachbe.; Handicraft; Papier-mcachbe.; Handicraft